4′, 6‐dimethoxyisoflavone‐7‐O‐β‐D‐glucopyranoside (wistin) is a peroxisome proliferator‐activated receptor γ (PPARγ) agonist that stimulates adipocyte differentiation. (12th April 2016) - Sanada, Matoki; Hayashi, Ryuichi; Imai, Yoshimasa; Nakamura, Fumiya; Inoue, Tomoyo; Ohta, Shinji; Kawachi, Hiroyuki
Abstract: Peroxisome proliferator‐activated receptor γ (PPARγ) is a ligand‐dependent transcription factor that directly activates the expression of adipocyte‐specific genes, and is universally accepted as the master regulator for adipocyte differentiation. Using a PPARγ luciferase reporter assay system, we showed that 4′, 6‐dimethoxyisoflavone‐7‐ O ‐β‐D‐glucopyranoside (wistin) dose‐dependently activates PPARγ. Treatment with wistin enhanced the marker of adipocyte differentiation, such as triglyceride accumulation in 3T3‐L1 cells. Real‐time quantitative polymerase chain reaction showed that wistin increased the expression of PPARγ2 messenger RNA. Moreover, the addition of wistin upregulated the expression of PPARγ‐target genes, aP2 and adiponectin in 3T3‐L1 cells. To our knowledge, wistin is the first isoflavonoid O ‐glycoside that exhibits PPARγ agonist activity.